a)
[tex]a^3 \times a^5 = a^{3+5} = a^8[/tex]
b)
[tex]a^6\times a^{-4} = a^{6+(-4)} =a^{6-4} = a^2[/tex]
c)
[tex]2a^2 \times 3ab = 6a^3b[/tex]
d)
[tex]3a^2b \times 5a^2b = 15a^4b^2[/tex]
e)
[tex]a^7 \div a^5 = a^{7-5} = a^2[/tex]
f)
[tex]a^6 \div a^{-4} = a^{6-(-4)} = a^{6+4} = a^{10}[/tex]
g)
[tex](f^2)^3 = f^6[/tex]
h)
[tex](3f^3)^2 = 3^2f^{3\times 2} = 9f^6[/tex]
i)
[tex](5f^{-4})^2 = 5^2 f^{-4\times 2} = 25f^{-8} = \frac{25}{f^8}[/tex]
j)
[tex]14^0 = 1[/tex]
k)
[tex] \frac{55e^5f^7}{5ef^2}= 11 e^{5-1} f^{7-2} = 11 e^4f^5[/tex]
l)
[tex] \frac{27e^4f^6}{3ef^6} =9e^{4-1}f^{6-6} = 9e^3f^0 = 9e^3[/tex]
m)
[tex]81^{\frac{1}{2}} = \sqrt{81} =9[/tex]
n)
[tex]64^{\frac{1}{2}} = \sqrt{64} =8[/tex]